IMPACT OF FENUGREEK SEED POWDER SUPPEMENTATION AMONG DIABETIC PATIENTS - Prabhulal, Sharda Kusumlatta; Patel, Hemlatta J. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Fenugreek seeds or methi seeds are an annual herb and use both as a spice and as a medicine. Fenugreek seeds are one of the common ingredients in many traditional cuisines. The benefits of fenugreek are widely studied. This herb has many positive effects on overall health if included in the diet regularly. Fenugreek is one of the oldest remedial plants, native to Central and Southeast Asia, especially India. However, it is also cultivated in North Africa, Mediterranean regions, and the US. Regular intake of fenugreek seed in any form leads to a good health. It is used for the treatment of so many disease conditions like Diabetes, Heart diseases, skin, hair, and stomach problems. It has a potential to control blood sugar and cholesterol level effectively. Present study was planned for the study of impact of fenugreek seed powder as a supplementation. For the study, case study approach was applied. For that total 30 diabetic respondents were selected purposively. Before and after supplementation, blood sugar was analyses at laboratory. The study concluded that fenugreek has a positive impact on the reduction and control of blood sugar level among diabetic patients.